Ten Tips to Consider When Creating and Screening PBIS Films. (August 2019) - Hirsch, Shanna E.; Brown, Courtney P.; Halley, Emma A.; Beach, John; MacSuga-Gage, Ashley S.; Spence, Sarah E.; Kennedy, Michael
School personnel can benefit from creating and sharing their own positive behavioral interventions and supports (PBIS) videos. PBIS videos can (a) introduce a new initiative to faculty and students, (b) teach specific school or class expectations, (c) reinforce appropriate student and staff behavior, and (d) celebrate PBIS implementation successes. This discussion article lists and describes strategies that can be used to create and screen PBIS videos. Examples of school personnel using PBIS videos are included.